Chiral Sensing with Mesoporous Pd@Pt Nanoparticles. Issue 8 (19th April 2017) - Fang, Yuxi; Li, Cuiling; Bo, Jiang; Henzie, Joel; Yamauchi, Yusuke; Asahi, Toru
Abstract: Mesoporous Pd@Pt nanoparticles possess high surface areas while still maintaining electroconductivity and low potential for agglomeration. By introducing L‐ or D‐DOPA (3, 4‐dihydroxyphenylalanine) enantiomers during the synthesis of the mesoporous Pd@Pt nanoparticles, we can create a Pt shell that is sensitive to the chirality of the DOPA molecule. We demonstrate sensitive electrochemical detection of DOPA enantiomers. Abstract : That makes sense : The synthesis of high‐surface‐area mesoporous Pd@Pt nanoparticles for chiral sensing is demonstrated. This is done by treating the nanoparticles with chiral molecules (D‐DOPA, and L–DOPA) during synthesis procedure, which imparts molecular affinity for the desired enantiomer and stereoisomer.